S1_2 Melting Mars - Mahmood, Ridda; Gajendran, Arcchana; Madden, Shannon (Physics Special Topics, 2017)
Unlike Earth, Mars lacks a fluid outer core to provide a global magnetic field to shield it against harmful solar winds. Mars is estimated to have a largely solid core of Iron, Nickel and Sulphur. We calculated 7:75 x10^13 kg of Uranium-235 would be needed in a theoretical bomb to liquify a proportion of Mars' core. The proportions used were a scaled imitation of Earth's core.